HELMINTH PARASITES OF FISHES OF AWANGSOI FISHERY, MANIPUR - PUINYABATI, H.; SHOMOREDRA, M.; VISHWESHWARI, A.; BINKY, KH.; KAR, DEVASHISH; JHA, A.N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
Present communication deals with helminth parasites of the fishes of Awangsoi Lake, Bishnupur, Manipur, India. The finding includes four nematodes namely, Procamallanus (Procamallanus) saccobranchi, Camallanus anahantis, Paraquimperia manipurensis and one juvenile stage of genus Syphacfa, five trematodes i.e. Allocreadium handiai, A. faciatusi and Astiotrema reniferum, Clinostomum complanatum and Genarcopsis goppo three cestodes i.e. Djombangia penetrans, Capingenioides singhi and Lytocestus bishnupurensis, and two acanthocephala i.e. Pallisentis ophiocephali and Acanthocephalus sp.